2009
DOI: 10.1088/1126-6708/2009/07/055
|View full text |Cite
|
Sign up to set email alerts
|

A pure-glue hidden valley I. States and decays

Abstract: It is possible that the standard model is coupled, through new massive charged or colored particles, to a hidden sector whose low energy dynamics is controlled by a pure Yang-Mills theory, with no light matter. Such a sector would have numerous metastable "hidden glueballs" built from the hidden gluons. These states would decay to particles of the standard model. We consider the phenomenology of this scenario, and find formulas for the lifetimes and branching ratios of the most important of these states. The d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
188
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(193 citation statements)
references
References 48 publications
5
188
0
Order By: Relevance
“…In the Folded SUSY and Quirky Little Higgs models, the mirror sector contains its own copy of a confining QCD-like force. Since LEP limits forbid mirror matter with masses below ∼ 100 GeV, the lightest states of the mirror QCD sector are mirror glueballs [51][52][53], which couple to the SM-like Higgs through a top partner loop. This interaction both allows the SM Higgs to decay to mirror glueballs with an appreciable branching ratio, and allows the produced glueballs to decay back in the SM with macroscopic lifetimes ∼ µm to km [54].…”
Section: Electroweak Top Partnersmentioning
confidence: 99%
“…In the Folded SUSY and Quirky Little Higgs models, the mirror sector contains its own copy of a confining QCD-like force. Since LEP limits forbid mirror matter with masses below ∼ 100 GeV, the lightest states of the mirror QCD sector are mirror glueballs [51][52][53], which couple to the SM-like Higgs through a top partner loop. This interaction both allows the SM Higgs to decay to mirror glueballs with an appreciable branching ratio, and allows the produced glueballs to decay back in the SM with macroscopic lifetimes ∼ µm to km [54].…”
Section: Electroweak Top Partnersmentioning
confidence: 99%
“…These glueballs decay through higher dimensional operators into SM matter. Depending on the scales, however, their lifetime may be very long [21,27], potentially leading to cosmological problems depending on the quirk masses and the confinement scale. In QDM, there are additional operators due to interactions with the Higgs.…”
Section: Field Contentmentioning
confidence: 99%
“…For theories with vector-like quirks, Refs. [21,27] showed that the glueballs decay slowly, since the leading operators are suppressed by many powers of the quirk mass. One such operator is…”
Section: Quirkcolor Glueball Decaymentioning
confidence: 99%
“…In other words, it gives an example of a "hidden valley" [55]. (In some ways such a scenario could resemble the physics of quirks [56] and of the pure-glue hidden valley [57], although the glue here is five-dimensional and involves additional modes associated with the S 4 . )…”
Section: Scales In D4-brane Theoriesmentioning
confidence: 99%